2016
DOI: 10.1063/1.4944487
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fe3O4 nanoparticles on positive streamer propagation in transformer oil

Abstract: Fe3O4 nanoparticles with an average diameter of 10 nm were prepared and used to modify streamer characteristic of transformer oil. It was found that positive streamer propagation velocity in transformer oil-based Fe3O4 nanofluid is greatly reduced by 51% in comparison with that in pure oil. The evolution of streamer shape is also dramatically affected by the presence of nanoparticles, changing from a tree-like shape with sharp branches in pure oil to a bush-like structure with thicker and denser branches in na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…For example, the chop time of oil-impregnated pressboard under positive lightning impulse voltages was prolonged by 72.8% when the electrode gap distance was 20 mm, and the improvement in chop time was still relatively large when the electrode gap distance was increased to 30 or 40 mm. These results are in accordance with our previous work on the streamer characteristics of Fe 3 O 4 nanofluid [18,22], indicating that Fe 3 O 4 nanoparticles can effectively restrain the process of creeping flashover at the oil/pressboard interface, thus extending the development time and reducing the average propagation speed of the positive streamer.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…For example, the chop time of oil-impregnated pressboard under positive lightning impulse voltages was prolonged by 72.8% when the electrode gap distance was 20 mm, and the improvement in chop time was still relatively large when the electrode gap distance was increased to 30 or 40 mm. These results are in accordance with our previous work on the streamer characteristics of Fe 3 O 4 nanofluid [18,22], indicating that Fe 3 O 4 nanoparticles can effectively restrain the process of creeping flashover at the oil/pressboard interface, thus extending the development time and reducing the average propagation speed of the positive streamer.…”
Section: Resultssupporting
confidence: 92%
“…From the above results, one conclusion that can be reasonably drawn is that, compared to that of OIP, the rapid surface charge decay rate in NIP is mainly attributable to its increased shallow traps density resulting from the addition of Fe 3 O 4 nanoparticles, which is consistent with our previous studies [7,22]. In particular, the creeping flashover usually starts from the weakest link of oil-impregnated pressboard.…”
Section: Resultssupporting
confidence: 90%
“…As in reality, mineral oil in the transformer is subjected to high voltages and currents, so the electrical stresses are applied to provide these conditions. During the operation, the transformer gets heated due to the heating effect of current and other power losses, so to provide the condition of higher temperature, thermal stresses are applied [16].…”
Section: Aging Processmentioning
confidence: 99%
“…This showed that a complete set of tests were not performed on the NFs, for which further tests are still needed to be performed. In the case of [16], SiO 2 NPs were added to mineral oil to observe any change in the dielectric and thermal properties of the NF. The primary test performed was the BV test to check the dielectric strength of the oil.…”
Section: Critical Analysis With Recent State-of-the-art Workmentioning
confidence: 99%
“…The mechanism of Fe 3 O 4 nanoparticle effect on the breakdown voltage was studied at a certain level. It was found that nanoparticles can inhibit space charge accumulation and uniform electric field in insulating oil [5]. Several studies have shown that nanoparticles increase the trapping density and depth, and reduce the velocity of streamer propagation in nanofluids [6,7].…”
Section: Introductionmentioning
confidence: 99%